Disposition of toxic drugs and chemicals in man - Baselt, Randall Clint 1944- (Seal Beach Biomedical Publications, 2020)
"The purpose of this work is to present in a single convenient source the current essential information on the disposition of the chemicals and drugs most frequently encountered in episodes of human poisoning. The data included relate to the body fluid concentrations of substances in normal or therapeutic situations, concentrations in fluids and tissues in instances of toxicity and the known metabolic fate of these substances in man. Brief mention is made of specific analytical procedures that are applicable to the determination of each substance and its active metabolites in biological specimens. It is expected that such information will be of particular interest and use to toxicologists, pharmacologists, clinical chemists and clinicians who have need either to conduct an analytical search for these materials in specimens of human origin or to interpret analytical data resulting from such a search"-- Provided by publisher.
Keywords: Drugs--Metabolism.; Xenobiotics--Metabolism.